PELAYANAN PUBLIK DI LEMBAGA PEMASYARAKATAN (STUDI LAYANAN PUBLIK DI LEMBAGA PEMASYARAKATAN KELAS IIA CIBINONG) - Henry Erwinton (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
Prisoners' rights as regulated in Law Number 12 of 1995 concerning Corrections, Article 14 are rights that must be fulfilled as a public service. Law Number 25 of 2009 concerning Public Servants aims to provide legal certainty in the relationship between the community and organizers. The implementation of Public Services is based on Article 4 of Law Number 29 of 2009 concerning Public Services related to the principles covering: a. Public interest; b. legal certainty; c. equal rights; d. balance of rights and obligations; e. professionalism; f. participation; g.equal treatment / non-discrimination; h. openness; i. accountability; j. special facilities and treatment for vulnerable groups; k. timeliness; and l. speed, convenience and affordability. Class IIA Cibinong Correctional Institution in providing services to the community strives to provide the best service in accordance with regulated provisions. Achieved not because the individualist organization neglects because of the cooperation or synergy between the Class IIA Cibinong Correctional Institution and the 3rd Party needed and supporting the public service program.